The Expression of Methyltransferase-Like 3 in Oral Precancerous Lesions and Oral Squamous Cell Carcinoma - Udompatanakorn, Chatchaphan; Taebunpakul, Patrayu (European Journal of Dentistry, 2022)
Objective N6-methyladenosine is the most frequent mRNA modification in eukaryotic cells. It is catalyzed by the methyltransferase complex, methyltransferase-like 3 (METTL3). Previous studies have revealed that METTL3 plays a role in various cancers. However, there is limited information about the roles of METTL3 in oral epithelial dysplasia (OED). This study determined METTL3 expression in normal oral mucosa (NOM), OED, and oral squamous cell carcinoma (OSCC) by immunohistochemistry.Materials and Methods Twenty formalin-fixed paraffin embedded specimens each of NOM, OED, and OSCC were included. The expression pattern, the number of positive cells, the staining intensity, and the histochemical score (H-score) of METTL3 were investigated.Statistical Analysis The data were analyzed by using one-way analysis of variance, chi-squared test, and a Kruskal–Wallis test. A p-value < 0.05 indicated statistically significant.Results The METTL3 expression in NOM was observed in the basal, parabasal, and lower layers of epithelium. In low-grade OED, METTL3 was expressed in the lower epithelial layers and partially presented in the spinous layer. However, in high-grade OED, METTL3 expression was observed in the lower layers, spinous layers, and upper layers of dysplastic epithelium. For OSCC, METTL3 immunostaining was presented in both the peripheral and central cells of the tumor islands. All NOM samples showed weak-to-moderate METTL3 staining intensity, while the moderate-to-strong METTL3 staining intensity was observed in 95% of both OED and OSCC specimens (p < 0.05). The percentage of METTL3 positive cells and H-score was highest in OSCC, followed by OED and NOM, respectively (p < 0.05). Interestingly, H-score was greater in high-grade OED (209.8 ± 18.61) when compared with low-grade OED (162.1 ± 38.93) (p < 0.05).Conclusion METTL3 expression in OED and OSCC was more outstanding than in NOM, suggesting possible roles for OED and OSCC pathogenesis. Additionally, METTL3 expression may be an indicator for OED progression to OSCC.
Keywords: oral epithelial dysplasia; oral squamous cell carcinoma; methyltransferase-like 3; immunohistochemistry